Dampak keberadaan villa bagi masyarakat di banjar canggu kuta bali - Sukradana, I Nengah; Jamin Ariana, I Nyoman; Ratna Sari, Putu (Jurnal Kepariwisataan dan Hospitalitas, 2018)
Abstract The purpose of this research is to know the development of villas within the last 5 years, the perception of society along with the economic, socio-cultural and environmental impacts that exist in Banjar Canggu Kuta Bali. Data collection in this research was done by observation method, structured interview, questionnaire, and library study by using qualitative descriptive data analysis technique. The results of this study: The development of villas from 2012 to 2016 has increased from 111 units to 245 units of villas. Based on the results of the research obtained through the analysis of public opinion about the impact of the existence of villas for the community in Banjar Canggu Kuta Bali using Likert scale that the economic impacts such as: Banjar Adat income (excellent), society income (excellent) employment opportunities for local society (enough), lend price are less productive (excellent), total and demand for marine fish products (excellent) opportunities for entrepreneurship or self-employment (excellent), socio-cultural impacts such as: level of security (excellent), social life society (excellent), imitation of lifestyle and culture of the tourists (enough), insight and outlook on the outside world (good), preservation of traditional arts and customs (excellent), and environmental impacts such as: preservation of environmental authenticity (not good) the beauty of the environment (excellent), maintenance and improvement of various public facilities (excellent), management of waste management or waste from oprasional villas (enough), pollution and environmental pollution (not good). So the impact of the existence of villas for society in Banjar Canggu Kuta Bali (good).   Keywords : Impact, Banjar Canggu society, and villa .